Staff management - Betts, P. W. (Plymouth : Macdonald and Evans, 1977)
This text is designed to illustrate how clerical, professional and technical staff may be more effectively managed, and encouraged to show enthusiasm and efficiency at work.
Includes index.
ne 12/07/2018
Loans
Keywords: Personnel management